Surgical Outcomes After Microvascular Decompression With Internal Neurolysis and Partial Neurectomy for Patients With Trigeminal Neuralgia and Negative Neurovascular Compression. (1st September 2019) - Carpenter, Amanda; Liu, James K
Abstract: INTRODUCTION: Microvascular decompression (MVD) is an effective and durable treatment for patients with trigeminal neuralgia (TN) due to neurovascular compression (NVC). In the absence of NVC, the traditional MVD is less effective in achieving long-term pain relief. Internal neurolysis at the root entry zone (REZ) of the trigeminal nerve has been described in the literature; however, there are few reports of long-term outcome after this procedure. Furthermore, this is the first study to combine this procedure with additional partial neurectomy. METHODS: This is a retrospective review of the senior author's patients with TN who underwent retrosigmoid craniectomy for MVD with internal neurolysis and partial neurectomy. Primary indications were patients with TN and no evidence of NVC intraoperatively. A total of 9 patients were included in the analysis. Three cases were of recurrent TN. The technique was performed with an 11-blade or arachnoid knife to open the perineurium in a longitudinal fashion at the REZ. A disc dissector was used to comb the fascicles along the longitudinal course, and a partial neurectomy was performed with a microscissors to make three selective cuts into the fascicles at the REZ. Barrow Neurological Institute (BNI) facial pain and numbness scales were used as postoperative assessment. RESULTS: At median follow up of 12 mo (range: 2 to 34), 8 of 9 patients (89%) had a BNI-pain score of I (no trigeminal pain, no medications). Two of nine patients (22%) had a BNI-numbness score of I (no numbness); seven (78%) had a BNI-numbness score of II (mild facial numbness that is not bothersome). CONCLUSION: Internal neurolysis with partial neurectomy appears to be an effective and potentially durable treatment option for patients with TN (primary or recurrent) without NVC. Larger series with longer follow-up is indicated to further evaluate the utility of this procedure.